STIMULASI PERKEMBANGAN BAHASA ANAK USIA DINI MELALUI MEDIA PEMBELAJARAN INTERAKTIF DI DENALI DEVELOPMENT CENTER - Rindri Suci Rodia (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
This activity aims to provide an overview of early childhood language development from learning stimulation activities through interactive video learning media at the Denali Development Center (DDC). Interactive video was chosen because it is considered very suitable for the characteristics of early childhood who tend to get bored easily, have low focus and concentration, and tend to be active and find it difficult to sit still. Based on the results of observations that have been made at DDC found problems where some children aged 1-3 years, experience speech delays where children cannot pronounce vocabulary correctly when communicating, the vocabulary mastered by children is still small, children cannot compose simple sentences when communicating, children have not been able to provide answers to questions that are given quickly and straightforwardly and the child has not been able to listen properly. From the results of the learning activities that have been carried out during the service period, gradually the child experiences significant language development where the child is quiet and never makes a sound or gives a slow reaction, this child begins to make sounds such as laughter or bubbling. And other children who cannot pronounce words correctly, gradually these children can say some words well and their meanings can be understood and the vocabulary they master also develops. Therefore providing stimulation to children is very important to reach this stage of development. Children who receive less stimulation tend to have problems and obstacles in their development.